Kekuatan Eksekutorial Akta Jaminan Fidusia terhadap Objek yang Dikuasai Negara - Juan Satria Mahendra; Noor Hafidah (Lembaga Yasin AlSys, 2026)
Although fiduciary security has been extensively regulated in Law Number 42 of 1999, studies that specifically discuss the executorial force of fiduciary deeds when the collateral object is controlled by the state remain limited. This study aims to analyze whether state confiscation eliminates creditors’ proprietary rights over fiduciary collateral objects and to formulate the legal construction of the position of fiduciary creditors regarding collateral objects confiscated by the state. This study used a normative legal method with a theoretical research type, through a statutory approach and a prescriptive conceptual approach. Legal materials were collected through library research and analyzed qualitatively using systematic interpretation and deductive reasoning. The results show that state confiscation does not automatically eliminate creditors’ proprietary rights because fiduciary security has the characteristic of droit de suite as affirmed in Article 20 of Law Number 42 of 1999 and grants creditors a preferential position based on Article 27 paragraph (1) of the same law. However, the absence of explicit regulation regarding the position of fiduciary creditors when collateral objects are confiscated by the state creates legal uncertainty and a conflict of norms between civil law and criminal law. The conclusion of this study emphasizes the importance of synchronizing fiduciary security law and criminal confiscation procedures so that the rights of bona fide third parties remain protected. The implications of this study provide theoretical contributions to the development of security law literature and practical implications for policymakers in formulating clear creditor protection mechanisms when fiduciary collateral objects are subject to state confiscation.